Sexual dimorphism in significant correlations frequency between the characteristics of body trunk and feet in children aged 4 to 6 years - Alicja Kaiser; Mirosław Mrozkowiak; Marek Sokołowski (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
Relatively few publications have concerned characteristics of body trunk and feet. It is generally suggested that correlations exist between the characteristics of the developing foot and the spinal column. The purpose of the study was to show sexual dimorphism in frequency of incidence, as well as significant correlations concerning selected body trunk and feet parameters in the group of 46-year-old children. The examinations conducted in a group of children aged 4 to 6 allowed for recording 2,988 observations, including 1,482 girls and 1,506 boys, and values of 87 characteristics that described body trunk and feet. The test stands for the measurement of the selected parameters using the photogrammetric method consisted of a personal computer, software, screen and printer, and a projection-reception device with a camera. The general number of body trunk characteristics having significant correlations with feet parameters in females was slightly higher. The number of relationships in sagittal and frontal planes was the same in both sexes. The characteristics that differentiated males from females were found mainly in transverse and frontal planes. The number of feet characteristics that most often showed significant correlations with body trunk parameters was higher in girls than in boys. These were mainly characteristics concerning width and length, longitudinal arch and disorders in the position of the feet. The characteristics that differentiated boys described only the longitudinal arch of the feet.